KNOWLEDGE ABOUT CROSS-COMPLIANCE POSSESSED BY FARMERS FROM OPOLSKIE VOIVODSHIP - Małgorzata Borkowska; Michał Kruszyński (Acta Scientiarum Polonorum. Oeconomia, 2012)
In the article there were presented the results of survey conducted in 2011, among 250 farmholders in the area of Opolskie Voivodship. The aim of research was determination of knowledge about cross-compliance possessed by agricultural producers from Opolskie Voivodship and consequences resulting from its realization. On the basis of research it is possible to state that the level of agricultural producers’ knowledge, regarding cross-compliance, is not satisfactory and, therefore, requires immediate filling. Investigation constitutes the part of broader research project involving the authors’ examination of the knowledge possessed by agricultural producers from southwest Poland about the mentioned subject. The articles published so far have referred to the knowledge about cross-compliance possessed by agricultural producers from Lower Silesia and Łódzkie Voivodship.